SPECIFIC ASPECTS OF DISEASES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND HUMAN IMMUNODEFICIENCY VIRUS CONCOMITANT - Barno Kh. Shagazatova; Feruza S. Mirkhaydarova (Central Asian Journal of Medicine, 2023)
In recent years, Type 2 diabetes has been growing rapidly in pictures and spreading rapidly among the younger class of the population. This is manifested by an increase in the number of cases of infection with HIV (human immunodeficiency virus), among other diseases. One of the characteristic features in the concomitant meeting of HIV infection and diabetes mellitus is associated with a sharp decompensation of glycemic indicators in patients and a strong influence on this by the Roxy-emotional state.